Poly (3, 3-dialkylquaterthiophene) Based Flexible Nitrogen Dioxide Gas Sensor - Kumar C.; Rawat G.; Kumar H.; Kumar Y.; Ratan S.; Prakash R.; Jit S. (My University, 2025)
A poly (3, 3-dialkylquaterthiophene) (PQT-12) based flexible metal-semiconductor-metal nitrogen dioxide (NO2) gas sensor fabricated on a flexible polyamide substrate has been reported in this article for the first time. The thin PQT-12 film deposited on the polyamide substrate is investigated by X-ray diffraction, atomic force microscopy, and scanning electron microscopy. The sensor shows a gas response of 24 with a response time of 41s at a very low concentration of 100-ppb NO2 gas under ambient air atmosphere. The gas response of 48 is measured at higher concentration of 500-ppb NO2 gas. The NO2 gas detection has been illustrated using a prototype circuit for the proposed sensor. © 2017 IEEE.